In vitro models for metabolic studies of small peptide hormones in sport drug testing. (3rd December 2014) - Esposito, Simone; Deventer, Koen; Geldof, Lore; Van Eenoo, Peter
<x xml:space="preserve">Abstract</x> Peptide hormones represent an emerging class of potential doping agents. Detection of their misuse is difficult due to their short half‐life in plasma and rapid elimination. Therefore, investigating their metabolism can improve detectability. Unfortunately, pharmacokinetic studies with human volunteers are often not allowed because of ethical constraints, and therefore alternative models are needed. This study was performed in order to evaluate in vitro models (human liver microsomes and S9 fraction) for the prediction of the metabolism of peptidic doping agents and to compare them with the established models. The peptides that were investigated include desmopressin, TB‐500, GHRP‐2, GHRP‐6, hexarelin, LHRH and leuprolide. Several metabolites were detected for each peptide after incubation with human liver microsomes, S9 fraction, and serum, which all showed endopeptidase and exopeptidase activity. In vitro models from different organs (liver vs. kidney) were compared, but no significant differences were recorded. Deamidation was not observed in any of the models and was therefore evaluated by incubation with α‐chymotrypsin. In conclusion, in vitro models are useful tools for forensic and clinical analysts to detect peptidic metabolic markers in biological fluids. Copyright © 2014 European Peptide Society and John Wiley & Sons, Ltd.